Has the current global financial crisis significantly affected momentum profitability? - Ahmad Ahmad; Adel Bino; Mohammad Tayeh (Cogent Business & Management, 2021)
In this study, we examine the behavior of stock price changes in an emerging market to search for possible momentum incidents. Our findings indicate that the existence of momentum can be characterized by the state of the economy, which is significantly correlated with the down market. We argue that this is due to investors, who have diminishing marginal utility of wealth and, in turn, behave in a risk-averse manner, resulting in loser portfolios being responsible for the vast majority of the observed momentum profitability. Furthermore, we find that momentum profitability is stronger with longer formation and holding periods, despite few cases of winners' return reversals. Our findings remain robust after controlling for size and book-to-market and earnings-to-market ratios.
Keywords: 650; momentum profits; global financial crisis; conservatism; size; earnings-tomarket; book-to-market